IN VITRO study of copper coordination compounds with thiosemicarbazone action on antioxidant enzymes (One Health & Risk Management, 2025)
Introduction. Thiosemicarbazones represent a class of organic compounds with significant pharmacological potential, known for their antitumor, antimicrobial, and antiviral activities. Recently, researchers have increasingly focused on how these compounds influence cellular redox balance, particularly through modulation of antioxidant system activity.  Thus, the study aimed to evaluate the antioxidant properties of selected thiosemicarbazones via in vitro experiments. Material and Methods. The research was performed on peripheral blood samples collected from 10 clinically healthy individuals. The compounds were tested at two concentrations (10.0 μmol/L and 1.0 μmol/L) to assess their impact on the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT). Results. The results revealed that certain thiosemicarbazones can impact the activity of SOD, and CAT in particular manner, thereby affecting cellular capacity to neutralize reactive oxygen species.Conclusion. Due to their ability to stimulate antioxidant responses, thiosemicarbazones emerge as promising platforms for the development of targeted therapeutic agents, particularly in cancer and degenerative disease treatment. In the current context of pursuing low-side-effect therapies that maintain cellular homeostasis, investigating the influence of thiosemicarbazones on the antioxidant system is a highly innovative research direction.
Keywords: copper coordination compounds with thiosemicarbazones; the supernatant; antioxidant enzymes